The Meaning Significance of Kenclung Bamboo Art in Gerduren Banyumas - Wijaya, Barkah Bangkit; Saputra, Dani Nur; Miyazawa, Naori (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2024)
Kerta Wijaya developed Kenclung bamboo art as a form of self-motivation in response to the dissatisfaction of farm laborers with agricultural products. The Gerduren Village community has implemented Kenclung art as a means of communication and entertainment while maintaining their rice fields. The researcher looks at the values in the Kenclung art based on the justifications. This study is qualitative. This study is being conducted in Gerduren, Banyumas Regency. Document studies, interviews, and observation were the methods used to obtain data. Triangulation is the data validity approach applied in this study. One method of data analysis was the Miles and Huberman model analysis. Axiological values were used to assess the Kenclung results. The activity reflects the divine value of many bamboo art values that are used in the study. Examples include the importance of religion in earthly alms, the reflection of a decent life in visiting family members, and the importance of truth in the community's traditional attire. The Banyumas community's ideals and customs are upheld by these garments, and beauty is judged by how people relate to one another, to God, and the natural world.